Research progress on thunderstorm asthma and its susceptibility factors - NAO Min; SHAN Hongwei (Yixue xinzhi zazhi)
Thunderstorm asthma refers to a pathological phenomenon in which the acute exacerbation of bronchial asthma or the worsening symptoms occurs due to the action of high concentrations of allergens on susceptible populations under specific meteorological conditions. As a public health issue, thunderstorm asthma can have adverse impacts on both individuals and society. This study reviews the pathogenesis of thunderstorm asthma, environmental triggers (pollen particles and air pollutants), meteorological triggers (relative humidity and temperature), individual susceptibility factors, as well as preventive and control measures, to provide references for related research on thunderstorm asthma and the development of public health policies.